Ethnobiology and Inuit health in a changing climate - Linnaea, Jasiuk; Pearce, T (ArcticNet Inc., 2013)
Ethnobiology is the scientific study of dynamic relationships among people, biota and environments. Traditionally Inuit depended on plants and animals to meet medicinal, nutritional and material needs; however, climate change and acculturation are resulting in the erosion of this body of knowledge simultaneous to the emergence of new health concerns and the passing of key knowledge holders, Elders. Inventories have been amassed documenting Inuit knowledge of plants and animals of ethnobiological significance; less is known about if, and how, this knowledge is being generated and transmitted in a contemporary Inuit community. Th e proposed research will work with community members in the Inuit hamlet of Ulukhaktok, Northwest Territories to examine the transmission of traditional knowledge of plant and animal uses for medicine and nutrition. Th e objectives are: (1) document the use of plants and animals for medicine and nutrition among Ulukhaktomuit; (2) identify key knowledge holders, how this knowledge was/is generated, and how/if this knowledge is being transmitted; (3) identify factors which aid or impede knowledge transmission; and (4) identify ways to promote ethnobiological knowledge in the community. Data will be collected using ethnographic research techniques including, free-listing, semi-structured and structured interviews, and participant observation. The research will be undertaken in collaboration with community partners and follow established protocols and guidelines for research in the community and region. It is hypothesized, based on the findings of ethnobotany research conducted elsewhere in the Canadian Arctic, that knowledge of the material uses of plants and animals will be more prevalent among community members than knowledge of their medicinal or nutritional uses. It is expected that this knowledge will be exclusive to only a few community members, likely Elders, and that the transmission of this knowledge will be incomplete. It is surmised that this knowledge still plays an important role in Inuit health and that knowledge transmission is crucial so that future generations can benefi t from the use of these resources. Th e research is part of the CIHR-funded project IKADAPT (Inuit traditional knowledge for adaptation to the health eff ects of climate change) [www.ikadapt.ca] and is additionally supported by the Nasivvik Centre for Inuit Health and Changing Environments.